The interaction of codes in dubbing: wordplay and visual restrictions - Martínez Tejerina, Anjana (MonTi Monografías de Traducción e Interpretación, 2014)
The following paper delves into the complex transfer of humour focusing on a recurring problem that appears when dubbing comedies: wordplay partially transmitted by image. It analyses the factors that have a bearing on translation and illustrates the various translation techniques with scenes from the Marx Brothers' filmography. Finally, it details the conclusions obtained from the analysis of the dubbing of 74 puns with visual restriction and its comparison with 116 cases where there is no such restriction.